Proyecto de factibilidad para la creación de una empresa productora y comercializadora de café tostado y molido de la parroquia Yangana del cantón Loja - Ortíz Vargas, Génesis Daniela (2019)
This investigation project named “Feasibility project for the creation of a productive and commercializing company of roasted and ground coffee from Yangana parish of the Loja canton”. It was realized in Loja city, with the general objective of: developing a project to determine the feasibility for the creation of a company that produces and sells roasted and ground coffee from Yangana parish of the Loja canton. For the elaboration of the project the methods that were used: deductive, inductive, analytical and synthetic, in addition to techniques such as: bibliographic compilation and survey, where a sample was determined that allowed to segment the population to be investigated, giving a total of 383 surveys applied to the families of the city of Loja. With this information, result that in city of Loja there is an unmet demand of 201.079 pounds of coffee, a marketing plan was elaborated to introduce the new product to the market and position it; the technical study determined the location which is in Marcopamba neighborhood from Yangana parish of the Loja canton; the project has an installed production capacity of 186.150 pounds of coffee, and a used capacity of 44.200 pounds of coffee, the same as the company keeps producing during the 5 years of the project; besides the flowcharts of processes and times, as well as the materials balance are also found in the technical study. The administrative study was carried out where the company was incorporated as an anonymous company, the organizational charts and manual of functions necessary for the operation of the company were drawn up. In the financial study the total investment was determined, which amounts to $19.116,33 dollars, this investment is financed by the contribution of the partners in 68,61% and a bank loan that finances the other part of the investment. In the financial evaluation, the feasibility of the project was verified by obtaining favorable results in the indicators such as: the NPV that results in $16.752,93 dollars, the IRR is 48,14%, the CBR is $ 0,13 cents and the PCR is 2 years, 9 months and 7 days. The sensitivity analysis shows that the project can support an increase in costs of up to 6,78% and a decrease in revenue of 6,01%.